2010
DOI: 10.1002/lary.21036
|View full text |Cite
|
Sign up to set email alerts
|

Decision making in head and neck cancer care

Abstract: Decision making in serious illness unfolds differently than in less serious problems. The conventional model does not fit this patient population, and reliance on trust of the physician figures prominently. Decision support should be aimed at physician decision making, promoting explicit incorporation of patient-specific data into the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…For example, up to 20 % of patients would accept a lesser chance of cure to avoid a laryngectomy and to keep their normal voice [ 3 , 4 ]. Hence, decisions on head and neck cancer treatment are widely recognized as being difficult [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, up to 20 % of patients would accept a lesser chance of cure to avoid a laryngectomy and to keep their normal voice [ 3 , 4 ]. Hence, decisions on head and neck cancer treatment are widely recognized as being difficult [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research has contributed to understandings of how people with a life‐threatening illness make sense of the factors that are important to them when they make decisions, why there may be interactional difficulties in the consultation and how they make sense of being asked to participate in decisions . For example, in a qualitative interview study of people at the end of life in three European countries, patients noted that doctors sometimes only gave information about the treatments that they preferred without discussing the ‘consequences of other actions’ .…”
Section: Introductionmentioning
confidence: 99%
“…A seminal study in the head and neck literature demonstrated through grounded theory analysis that head and neck patients, who are often in considerable pain and distress, do not make decisions according to the conventional shared decision‐making model. Patients focus on a “decision to do something” more than choosing a specific treatment and they rely heavily on a trust relationship with their physician . This study also noted that head and neck patients tend to move sequentially through different consulting specialists who may each offer a form of index treatment.…”
Section: Medical Decision Makingmentioning
confidence: 82%